DIAGNOSTIC ASSESSMENT AS THE FOUNDATION FOR ADAPTIVE AND DIFFERENTIATED LEARNING TRANSITION TO THE MERDEKA CURRICULUM - Sintya Rahmadewi; Ikhwanul Habib; Taqiyuddin Kabalmay (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
Diagnostic assessment plays a crucial role in the successful implementation of the Merdeka Curriculum, as it provides a foundation for adaptive, responsive, and differentiated learning. This study aims to offer a comprehensive understanding of the role of diagnostic assessment in identifying students’ readiness, learning needs, strengths, and weaknesses, as well as their socio-emotional conditions. Using a descriptive qualitative approach with library research as the main method, this study analyzes various sources, including official modules from the Ministry of Education and Culture, scientific journals, reference books, and relevant previous studies. The findings indicate that diagnostic assessment, classified into cognitive and non-cognitive types, enables teachers to design effective instructional strategies, implement remedial and enrichment programs, and foster collaboration among educators. Despite its advantages, diagnostic assessment also presents challenges such as potential misinterpretation, time constraints, and the need for adequate teacher training. Overall, diagnostic assessment serves not only as an instrument to measure student readiness but also as a theoretical construct that bridges curriculum objectives with learner diversity, thereby strengthening the foundation of differentiated and holistic education in the Merdeka Curriculum.